An improved method for using a microsatellite in the rice waxy gene to determine amylose class - Bergman, C.J.; Delgado, J.T.; McClung, A.M.; Fjellstrom, R.G. (Wiley, 2001)
Rice (Oryza sativa L.) breeders must evaluate progeny across multiple years and locations in part due to environmental effects on amylose content, the primary constituent that influences rice end‐use quality. A microsatellite correlated with the various classes of apparent amylose content in rice has been used to decrease the development time for the U.S. cultivars Cadet and Jacinto by several years. The objective of this project was to develop a relatively inexpensive method for assaying this microsatellite that is suitable for screening large numbers of progeny and to evaluate this method by analyzing a diverse set of breeding lines and cultivars. Rapid multiple‐kernel (brown and milled), single kernel, and leaf tissue alkali DNA extraction procedures were developed. Enhanced resolution of allele classes and separation speed was achieved by electrophoresing polymerase chain reaction (PCR) amplification products encompassing the waxy microsatellite in a polyacrylamide and Spreadex gel matrix using a triple‐wide mini electrophoresis unit. For germ plasm characterization, allele scoring accuracy and speed were improved by loading standards, consisting of three microsatellite classes in a single lane, several times across the gel. The microsatellite explained 88% of the variation in the apparent amylose content of 198 nonwaxy U.S. cultivars and breeding lines of diverse parentage, grown in four locations. The utility of this method was demonstrated by one technician analyzing a breeding population of 142 progeny in 1.5 days using relatively inexpensive laboratory equipment.